Anthony Angelo - Barton, George P (Victoria University of Wellington Law Review, 2008)
The author, having served as his lecturer, provides a tribute to Professor Angelo of the Law Faculty at Victoria University of Wellington. The article recalls Professor Angelo's instrumental role in bringing Comparative Law to the law school, as well as playing an important part in providing academic hospitality to visiting scholars. The author praises Professor Angelo's encyclopaedic knowledge on Comparative Law, and states that the University owes him a real debt for his commitment to expand and diversify law teaching, research, and writing.